The Role of Fortified and Enriched Refined Grains in the US Dietary Pattern: A NHANES 2009–2016 Modeling Analysis to Examine Nutrient Adequacy - Papanikolaou, Yanni; Fulgoni, Victor L. III (Frontiers in Nutrition, 2021)
Abstract Background: While dietary recommendations call for greater whole grain intake and reduced refined grain consumption, there are limited peer-reviewed studies examining the influence of fortified/enriched refined grains on nutrient adequacy. Methods: A modeling analysis using data from NHANES 2009-2016 estimated usual daily intake for Dietary Guidelines for Americans’ shortfall nutrients in the current dietary pattern and when specified percentages of all fortified/enriched refined grain foods (breads, ready-to-eat cereals, all grain foods) were removed from the diet (adults 19-50 yrs-old, N=11,169; 51-99 yrs-old, N=9,641). Results: While American adults are currently falling short of nutrient recommendations, eliminating 25, 50 and 100% of all grains consumed in the US dietary pattern resulted in a greater percentage of adults not meeting recommendations for several shortfall nutrients, including dietary fiber, folate DFE, iron, and magnesium. Removal of all grains led to a reduced energy intake by approximately 10% in both age groups examined. Currently, approximately 3.8% of 19-50 year-old adults meet the Adequate Intake for dietary fiber. Removal of 25, 50 and 100% of grains from the diet resulted in 2.6±0.3, 1.8±0.2, and 0.7±0.1% of adults exceeded the AI for dietary fiber, respectively. Similarly, 11.0 and 13.8% of younger and older adults, respectively, fall short of folate, DFE recommendations with the current diet. Following the removal of 100% of grains from the diet, 43.4±1.1 and 56.2±1.0%, respectively were below the Estimated Average Requirement (EAR) for folate DFE. For iron, current dietary pattern consumption shows 8.4 and 0.8% of younger and older adults, respectively, are not meeting iron recommendations, however, removal of 100% of grains from the diet results to nearly 10 and 22% falling short of the EAR. Currently, about 51 and 54% of younger and older adults, are below the EAR for magnesium, however, with the removal of 100% of grains, 68 and 73%, respectively, fall below the EAR. Conclusion: Removal of specific refined grains led to an increased percentage of Americans not meeting recommendations for several shortfall nutrients, including dietary fiber, folate, iron and magnesium.